A teoria, a prática, o professor e a educação ambiental: algumas reflexões - Teixeira, Lucas André [UNESP]; Reis, Marília Freitas de Campos Tozoni [UNESP]; Talamoni, Jandira Liria Biscalquini [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2011)
The acceleration of economic and scientific development caused by the production system and mechanistic science, have created new power structures and new political and social problems, including environmental ones, consolidating a period of widespread crisis in different spheres of society. In this context, reflection about the major causes of environmental problems is necessary in the field of environmental education. Therefore, considering that the current environmental crisis is directly related to the mode and the devices of production of the capitalist system, initiatives on environmental education should reflect, from a historical and dialectical process, on what is advocated by capitalist society. Considering the various theoretical-practical concepts and approaches in environmental education, the principles of Critical Environmental Education can provide conditions to confront the structural crisis that we are facing, through the educational process. It is a political process of reflection and critical appropriation of knowledge, attitudes, values and behaviors that aims to contribute to build a sustainable society from the social and environmental points of view. We intend to articulate it through the theoretical formulations of Historical-Critical Pedagogy with the purpose of presenting a reflection that may contribute to a pedagogic response to environmental issues, especially regarding the formation of teachers who develop projects in schools. Thus, this present study intends to highlight the contributions of the philosophy of praxis in the formation of environmental educators, grounded in theoretical aspects of Critical Environmental Education.

A aceleração dos desenvolvimentos econômico e científico causada pelo sistema de produção e pela ciência mecanicista fez surgir novas estruturações de poder e novos problemas políticos e sociais, inclusive os ambientais, consolidando-se, assim, um período de crises disseminadas nos vários âmbitos da sociedade. Em tal conjuntura, a reflexão sobre as principais causas da problemática ambiental apresenta-se como necessidade para o campo da educação ambiental. Considerando, portanto, que a atual crise ambiental está diretamente relacionada ao modo e aos meios de produção do sistema capitalista, entende-se que as iniciativas no âmbito da educação ambiental devem refletir, a partir de um processo histórico e dialético, sobre o que preconiza a sociedade do capital. Diante das diversas concepções e abordagens teórico-práticas existentes na educação ambiental, os princípios da educação ambiental crítica podem criar condições para o enfrentamento da crise estrutural que estamos vivenciando, a partir do processo educativo. Entendida como um processo político de apropriação crítica e reflexiva de conhecimentos, atitudes, valores e comportamentos, que tem como objetivo contribuir para a construção de uma sociedade sustentável do ponto de vista ambiental e social, pretendemos articulá-la às formulações teóricas da Pedagogia Histórico-Crítica, com vistas a apresentar uma reflexão que contribua para o enfrentamento pedagógico da questão ambiental, especialmente no que diz respeito à formação dos professores que desenvolvem projetos no âmbito escolar. Assim, o presente estudo objetiva evidenciar as contribuições da filosofia da práxis na formação do educador ambiental, tendo como fundamentação os pressupostos teóricos inseridos na vertente da educação ambiental crítica.
Theory, practice, teachers and environmental education: some reflections
Keywords: Environmental education; Teacher training; Pedagogical praxis; Educação ambiental; Formação de professores; Práxis pedagógica